Explanation:
The easiest thing to do here is:
4x + 2 = -2 and 4x + 2 = 26
Just know whaever you get for x is greater or less than the actual answer.
4x + 2 = -2
- 2 - 2
4x = -4
![(4x)/(4) = (-4)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p245knktr6akwdi924yiktwbrurhlvv5u5.png)
x = -1 <--- Because -2 is supposed to be greater than x, x equals any number less than -1 but not -1.
4x + 2 = 26
- 2 - 2
4x = 24
![(4x)/(4) = (24)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u38n3nyo6fqatpw4e1y0ru7000nckc7axd.png)
x = 6 <--- Because 26 is supposed to be less than x, x equals any numbey greater than 6 but not 6